Co-inoculation with rhizobia and arbuscular mycorrhizal fungi in seedlings of Prosopis laevigata - Crespo Flores, Gustavo; Ramírez-Tobias, Hugo M.; Vallejo-Pérez, Moises Roberto; Méndez-Cortés, Heriberto (Revista Mexicana de Ciencias Agrícolas, 2021)
Inoculation with rhizobia and arbuscular mycorrhizal fungi (HMA), single or combined, may contribute to the growth and establishment of Prosopis laevigata because of a positive interaction of symbionts with the plant. The objective was to evaluate the effect of single and combined inoculation of three local isolates of rhizobia (R1, R2 and R3) and two strains of HMA (HMA1 and HMA2) on mycorrhizal colonization, nodulation, growth and biomass production of P. laevigata in substrate with pH close to neutrality. The experiment was carried out in a greenhouse, at the Faculty of Agronomy and Veterinary of the UASLP in 2020-2021. Thirteen treatments were evaluated in a completely randomized design with five repetitions. The variables studied were number of spores g-1 of substrate, mycorrhizal colonization and visual density, total nodules, effective nodules, number of leaflets, height, stem diameter and biomass yield. Inoculation promoted greater colonization, nodulation and plant growth with respect to the non-inoculated control. With HMA1, HMA2, R1, R3, R1+HMA1, R3+HMA1, R1+HMA2 and R3+HMA2, results superior to those of the rest of the treatments were obtained. It is concluded that inoculation with local isolates of rhizobia and their combination with HMA favors the development of mycorrhizal structures, nodulation, growth and biomass production of P. laevigata grown in substrate with neutral pH. Isolates R1, R3, strains HMA1, HMA2 and combinations R1+HMA1, R1+HMA2, R3+HMA1 and R3+HMA2 were registered as effective inoculants to increase the growth of P. laevigata.